Epiretinal Membranes in Patients with Uveitis: Morphological and Functional Analysis with Spectral Domain Optical Coherence Tomography. (5th November 2013) - Iannetti, Ludovico; Tortorella, Paolo; D'Ambrosio, Enzo; Spena, Rossela; Zito, Roberta; Gharbiya, Magda
Abstract : Purpose . To correlate the uveitic epiretinal membrane (ERM) features using spectral-domain optical coherence tomography (SD-OCT) with visual acuity (VA). Methods . Forty-one eyes of 32 patients were included in this retrospective study. SD-OCT was performed in all patients and data were collected at the time of ERM diagnosis and at the final visit. Both best corrected visual acuity (BCVA) and ERM thickness were correlated with the morphological and clinical features. Results . Final BCVA was positively correlated with male sex ( P = 0.0055 ) and the focal pattern of ERM attachment ( P = 0.031 ) and negatively correlated with IS/OS photoreceptor junction disruption ( P = 0.042 ) . BVCA change showed a positive correlation with the age of ERM onset ( P = 0.056 ) but a negative correlation with IS/OS photoreceptor disruption at the ERM diagnosis ( P = 0.029 ) and the increase of central subfield thickness (CST) ( P = 0.95 ) . Final ERM thickness correlated with the duration of uveitis ( P = 0.0023 ) and the duration of ERM ( P = 1.15   e- 05 ) . During the follow-up, ERM thickening correlated with male sex ( P = 0.042 ), posterior uveitis ( P = 0.036 ), uveitis duration ( P = 0.026 ), and broad attachment pattern ( P = 0.052 ) . Conclusions . In the uveitic ERM, VA negatively correlates with IS/OS photoreceptor junction disruption and the increase of CST. ERM thickness is influenced by longer duration of both uveitis and ERM.